A Perspective on Implementing Movement Sonification to Influence Movement (and Eventually Cognitive) Creativity - Oppici, Luca; Frith, Emily; Rudd, James (Frontiers in Psychology, 2020)
Creativity represents an important feature in a variety of daily-life and domain-specific contexts. Recent evidence indicates that physical movement serves as a key resource for exploring and generating task-relevant creative ideas, supporting the embodied perspective on creative cognition. An intuitive link between movement and creative cognition is movement creativity. The process of exploring the movement solutions an environment offers (i.e., affordances) and exploiting novel, functional, and creative movements may translate to and improve how individuals explore and generate novel ideas. Opening perception to the variety of affordances (‘conventional’ and novel) an environment offers drives creative movement. Teachers and coaches can promote this process by designing a learning environment that invites performers to consider and utilize novel movement solutions. In this article, we present a rationale for using movement sonification to promote creative movement. Movement sonification consists of mapping a movement parameter into sound, with a sound being triggered or changing according to how movement unfolds. We argue that movement sonification can facilitate the emergence of creative movement via enhancing perception of currently performed movements and invite performers to utilize novel affordances, and emphasizing information for regulating subsequent creative actions. We exemplify this concept in a creative dance intervention for children during physical education classes. In conclusion, we contend that learning to explore original dance sequences using movement sonification may provide a meaningful link between creative movement and creative cognition. Children may use their minds and bodies as tools for creative thinking and exploration, such as shaping letters with their bodies.